Tonsillar tuberculosis : A case report - Karki, S; Karki, D (Journal of Pathology of Nepal, 2016)
Tuberculosis of the oral cavity which is an uncommon occurrence can be primary or secondary. In the absence of active pulmonary tuberculosis, isolated tonsillar tuberculosis is rare. Herein, we report two cases of bilateral tonsillar tuberculosis who presented as recurrent sore throat for which tonsillectomy was done. No active primary pulmonary lesion was found in these cases. Histopathological examination revealed caseating epithelioid granulomas with Langhans giant cells. Ziehl Neelson stain for acid fast bacilli was positive in one case. Tonsillar tuberculosis, though a rare entity, should be considered in the clinical differential diagnosis of tonsillar lesions. Histopathological examination with Ziehl Neelson stain should be performed for definite diagnosis.